2017
DOI: 10.1364/boe.8.000776
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit dependence of flow signal in optical coherence tomography angiography

Abstract: Abstract:The hematocrit dependence of flow signal (split-spectrum amplitude decorrelation angiography-SSADA decorrelation value) was investigated in this paper. Based on the normalized field temporal correlation function and concentration dependent particle scattering properties, the relationship between hematocrit and flow signal was analytically derived. Experimental verification of the relationship was performed with custom-designed microfluidic chips and human blood with 45%, 40% and 32% hematocrit. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In this regard, the identification of intra- and extra-ocular factors, which affect blood flow properties and thus OCTA measurements is of central interest. [410] We have recently reported that OCTA measurements can be altered by a physical exercise intervention. After a controlled short term (4-weeks) high-intensity interval training period, FDsM and FDnhPP values were changed and a strong effect on the FAZ area was observed, which was reduced by ~ 14%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the identification of intra- and extra-ocular factors, which affect blood flow properties and thus OCTA measurements is of central interest. [410] We have recently reported that OCTA measurements can be altered by a physical exercise intervention. After a controlled short term (4-weeks) high-intensity interval training period, FDsM and FDnhPP values were changed and a strong effect on the FAZ area was observed, which was reduced by ~ 14%.…”
Section: Discussionmentioning
confidence: 99%
“…A significant effect of haematocrit on the decorrelation signal using 45%, 40% and 32% haematocrit blood samples has been described in an ex-vivo model. [4] In our study, haematocrit values were determined in twelve randomly selected participants without significant differences in haematocrit values. However, this sample may not allow to fully exclude any effects of the haematocrit in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires a longer enough time interval between adjacent repeated B‐scans and enough number of repetitions at the same B‐scan location. We found that the optimum time interval was 5 ms when only two B‐scan at the same location was used . So in this study, we set the B‐scan time interval to 5 ms for widefield imaging to keep the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The model was calibrated using a laboratory phantom that used ex vivo human blood flowing through a microfluidic chip. 12 , 13 …”
Section: Methodsmentioning
confidence: 99%